If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + x = 6x + 63 Reorder the terms: 3 + x = 63 + 6x Solving 3 + x = 63 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + x + -6x = 63 + 6x + -6x Combine like terms: x + -6x = -5x 3 + -5x = 63 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -5x = 63 + 0 3 + -5x = 63 Add '-3' to each side of the equation. 3 + -3 + -5x = 63 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 63 + -3 -5x = 63 + -3 Combine like terms: 63 + -3 = 60 -5x = 60 Divide each side by '-5'. x = -12 Simplifying x = -12
| 1*2*3*4*5*6*7*8*9*10*11*12*13*14*15*16*17*18*19*20*21*22*23*24*25*26*28*29*30=x | | 7=12-3x | | 3(2x+5)-3=2(4x-8)+8 | | n^2+2n=2400 | | 5-3x+6x=29 | | 1-xy-x+y=0 | | 2x+4=6x-6 | | -6(5+3x)=-30 | | 7x+8=8-5x | | 4x+4=28+2x | | In(c)=In(19)-.08t | | 7+2q=6q-5 | | 3P=1765-2(31) | | K^2/16=6 | | 31=1765-2Q | | 9m^2-2=32 | | y^6+x^3=y^2+11x | | 11x+x^3=0 | | 3a^2+11=267 | | 3a^2+11=237 | | 3a^2+11=13 | | 9k^2+10=13 | | 8x^3-6x-4=0 | | 91=1765-2Q | | a^-7f/12g^-5 | | 7n-8-5=11-2n+y | | -6(x+90)=39(x+9) | | 12xy+3cx+9cy+8x= | | ax+4x+4y+ay= | | 5-3k=20 | | 3(4d-2)=21 | | -17-6= |